A system approach tho analysis of traffic dynamics - Figueiredo, Lino (2004)
This paper presents the Simulator of Intelligent Transportation Sytems (SITS), The SITS is based on a miscroscopic simulation approach to reproduce real traffic conditions in an urban or non-urban network and considers different types of vehicles, drivers and roads. A dynamical analysis of several traffic phenomena is then addressed. The results of using classical system theory tools point out that it is possible to study traffic systems, taking advantage on the knowledge gathered with automatic control algorithms. In this line of thought, it was also presented a new modelling formalism based on embedding of statisitcs and Fourier transform.